Pancreatic paracoccidioidomycosis simulating malignant neoplasia: case report - Lima, Talles Bazeia [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Caramori, Carlos Antonio [UNESP]; Silva, Giovanni Faria [UNESP]; Oliveira, Cássio Vieira de [UNESP]; Yamashiro, Fábio da Silva [UNESP]; Franzoni, Letícia de Campos [UNESP]; Sassaki, Lígia Yukie [UNESP]; Romeiro, Fernando Gomes [UNESP] (Baishideng Publishing Group, 2013)
Paracoccidioidomycosis is a systemic granulomatous disease caused by fungus, and must be considered in the differential diagnosis of intra-abdominal tumors in endemic areas. We report a rare case of paracoccidioidomycosis in the pancreas. A 45-year-old man was referred to our institution with a 2-mo history of epigastric abdominal pain that was not diet-related, with night sweating, inappetence, weight loss, jaundice, pruritus, choluria, and acholic feces, without signs of sepsis or palpable tumors. Abdominal ultrasonography (US) showed a solid mass of approximately 7 cm × 5.5 cm on the pancreas head. Abdominal computerized tomography showed dilation of the biliary tract, an enlarged pancreas (up to 4.5 in the head region), with dilation of the major pancreatic duct. The patient underwent exploratory laparotomy, and the surgical description consisted of a tumor, measuring 7 to 8 cm with a poorly-defined margin, adhering to posterior planes and mesenteric vessels, showing an enlarged bile duct. External drainage of the biliary tract, Rouxen-Y gastroenteroanastomosis, lymph node excision, and biopsies were performed, but malignant neoplasia was not found. Microscopic analysis showed chronic pancreatitis and a granulomatous chronic inflammatory process in the choledochal lymph node. Acid-alcohol resistant bacillus and fungus screening were negative. Fine-needle aspiration of the pancreas was performed under US guidance. The smear was compatible with infection by Paracoccidioides brasiliensis. We report a rare case of paracoccidioidomycosis simulating a malignant neoplasia in the pancreas head.
Keywords: Paracoccidioidomycosis; Pancreas; Fungus infection; Pancreatic tumors; Differential diagnosis